Regulatory T cells in neurological disorders and tissue regeneration: Mechanisms of action and therapeutic potentials - Jing Jie; Xiaomin Yao; Hui Deng; Yuxiang Zhou; Xingyu Jiang; Xiu Dai; Yumin Yang; Pengxiang Yang (Neural Regeneration Research, 2026)
Regulatory T cells, a subset of CD4+ T cells, play a critical role in maintaining immune tolerance and tissue homeostasis due to their potent immunosuppressive properties. Recent advances in research have highlighted the important therapeutic potential of Tregs in neurological diseases and tissue repair, emphasizing their multifaceted roles in immune regulation. This review aims to summarize and analyze the mechanisms of action and therapeutic potential of Tregs in relation to neurological diseases and neural regeneration. Beyond their classical immune-regulatory functions, emerging evidence points to non-immune mechanisms of regulatory T cells, particularly their interactions with stem cells and other non-immune cells. These interactions contribute to optimizing the repair microenvironment and promoting tissue repair and nerve regeneration, positioning non-immune pathways as a promising direction for future research. By modulating immune and non-immune cells, including neurons and glia within neural tissues, Tregs have demonstrated remarkable efficacy in enhancing regeneration in the central and peripheral nervous systems. Preclinical studies have revealed that Treg cells interact with neurons, glial cells, and other neural components to mitigate inflammatory damage and support functional recovery. Current mechanistic studies show that Tregs can significantly promote neural repair and functional recovery by regulating inflammatory responses and the local immune microenvironment. However, research on the mechanistic roles of regulatory T cells in other diseases remains limited, highlighting substantial gaps and opportunities for exploration in this field. Laboratory and clinical studies have further advanced the application of regulatory T cells. Technical advances have enabled efficient isolation, ex vivo expansion and functionalization, and adoptive transfer of regulatory T cells, with efficacy validated in animal models. Innovative strategies, including gene editing, cell-free technologies, biomaterial-based recruitment, and in situ delivery have expanded the therapeutic potential of regulatory T cells. Gene editing enables precise functional optimization, while biomaterial and in situ delivery technologies enhance their accumulation and efficacy at target sites. These advancements not only improve the immune-regulatory capacity of regulatory T cells but also significantly enhance their role in tissue repair. By leveraging the pivotal and diverse functions of Tregs in immune modulation and tissue repair, regulatory T cells–based therapies may lead to transformative breakthroughs in the treatment of neurological diseases.